InDesign for QuarkXPress users - Blatner, David (Peachpit Press, 2003)
While QuarkXPress is the most-widely used page-layout program in the world, Adobe InDesign is rapidly gaining ground with better typography and transparency features, speedier performance, and more overall control. Plus, InDesign 2 is Mac OS X native, QuarkXPress 5 isn't. But if you're a QuarkXPress user thinking of making the switch to InDesign, you know you can't afford to lose time and productivity at the office while learning a new program. Thanks to InDesign for QuarkXPress Users, you don't have to. InDesign for QuarkXPress Users is the only book on the market that shows experienced graphic designers how to use InDesign from a QuarkXPress user's perspective. Using an easy-to-read and easy-to-digest style, this unique title focuses on common tasks, giving you quick solutions rather than bogging you down with lengthy theory. Written by well-known experts in the field, the book is abundantly illustrated and covers topics such as using InDesign's transparency features (possible in QuarkXPress only by unwieldy workarounds), and making the most of master pages and style sheets. It's also loaded with real-world tips on how you can apply your QuarkXPress know-how to this up-and-coming software.